Effect of partner violence in adolescence and young adulthood on blood pressure and incident hypertension. - Cari Jo Clark (Public Library of Science (PLoS), 2014)
Intimate partner violence has adverse health consequences, but little is known about its association with hypertension. This study investigates sex differences in the relationship between intimate partner violence and blood pressure outcomes. Data included 9,699 participants from waves 3 (2001-02) and 4 (2008-09) of the National Longitudinal Study of Adolescent Health (51% female). Systolic (SBP) and diastolic (DBP) blood pressure and incident hypertension (SBP≥140 mmHg, DBP≥90 mmHg, or taking antihypertensive medication) were ascertained at wave 4. Intimate partner violence was measured at wave 3 with 8 items from the revised Conflict Tactics Scales. Separate victimization and perpetration scores were calculated. Sex-specific indicators of severe victimization and perpetration were created using the 66th percentile among those exposed as a cut point. Sex-specific, linear and logistic regression models were developed adjusting for age, race, financial stress, and education. Thirty-three percent of men and 47% of women reported any intimate partner violence exposure; participants were categorized as having: no exposure, moderate victimization and / or perpetration only, severe victimization, severe perpetration, and severe victimization and perpetration. Men experiencing severe perpetration and victimization had a 2.66 mmHg (95% CI: 0.05, 5.28) higher SBP and a 59% increased odds (OR: 1.59, 95% CI: 1.07, 2.37) of incident hypertension compared to men not exposed to intimate partner violence. No other category of violence was associated with blood pressure outcomes in men. Intimate partner violence was not associated with blood pressure outcomes in women. Intimate partner violence may have long-term consequences for men's hemodynamic health. Screening men for victimization and perpetration may assist clinicians to identify individuals at increased risk of hypertension.